Students’ Perceptions of the Use of ICT in Introduction to Literature Class - Meria Zakiyah Alfisuma; Tri Pujiati; Hendra Sudarso; Mariyatul Kiptiyah; Tera Athena (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Advancements in technology have facilitated a more accessible learning experience for students, with the integration of Information and Communication Technology (ICT) emerging as a prominent trend in the study of literary works. This qualitative descriptive study aims to explore students' perspectives on the use of ICT in the Introduction to Literature curriculum. Understanding students' viewpoints on ICT usage in this context serves as valuable evaluation material, enabling educators to formulate new policies pertaining to instructional methods for future Introduction to Literature courses. Data for this research was gathered through a questionnaire administered via Google Form to students enrolled in the Introduction to Literature course, yielding responses from 52 participants who randomly selected from students who had taken the Introduction to Literature course at STKIP PGRI Bangkalan. The collected questionnaire data was subjected to analysis involving data reduction, interpretation, and the formulation of conclusions. The findings reveal a highly positive outlook among students regarding the integration of ICT into their learning experience. A significant majority, 51.92%, expressed agreement with the incorporation of ICT in Introduction to Literature instruction. The presence of ICT has notably heightened students' enthusiasm for engaging with the subject matter. This research suggests that ICT can be effectively utilized in Introduction to Literature education through the implementation of diverse, engaging, and unique media, facilitating enhanced comprehension of the material by students.